The Effect of Webtoon Media on Reading Comprehension Skills of Fifth-Grade Students at SD Negeri 2 Sumber - Rama Liyya; Widia Nur Jannah; Dewi Yulianawati (Journal of Educational Sciences, 2026)
Reading comprehension is a fundamental literacy skill that enables students to understand, interpret, and construct meaning from written texts. This study aimed to examine the effect of Webtoon media on the reading comprehension skills of fifth-grade students at SD Negeri 2 Sumber. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of 48 fifth-grade students, including 24 students in the experimental class and 24 students in the control class. Data were collected through a reading comprehension test and a student response questionnaire and were analyzed using the Mann–Whitney U test because the data were not entirely normally distributed. The results revealed a significant difference between the experimental and control groups after the intervention (p = 0.002). Furthermore, the medium effect size (r = 0.455) indicates that the implementation of Webtoon produced a meaningful educational effect on students' reading comprehension skills. Students also showed positive responses toward the use of Webtoon, with an overall response rate of 80.44%, categorized as good. These findings indicate that Webtoon is an effective instructional medium for improving elementary students' reading comprehension skills and can be considered an alternative digital medium to support literacy instruction in elementary schools.